Metabolite profiling reveals the involvement of aberrant metabolic changes in Gentiana triflora seed showing poor germination. Issue 2 (3rd March 2016) - Takahashi, H.; Fujita, K.; Yoshida, C.; Nishihara, M.
ABSTRACT: Gentians are alpine plants and two endemic species, Gentiana triflora and G. scabra, are cultivated as ornamentals in Japan. Because most of the Japanese cultivars are F1 hybrids, seed germination rate is an important factor for maintaining these cultivars. However, germination rates frequently differ among cultivars. Poor germination is a severe problem for gentian production, although there is almost no difference in their germination period and growth rate. In this study, we compared seed germination rates among three cultivars of G. triflora . A high rate of seed germination was observed in 'Majel' (MJ) and 'Iwate' (IW), but a low rate was recorded in 'Iwate-Yumeminori' (YM). We conducted a targeted metabolome analysis using these cultivars to elucidate the potential cause of inhibited seed germination. Multivariate analysis revealed that the aberrant accumulation of specific amino acids and a decrease in energy metabolites were observed in YM seed. Furthermore, protein concentrations and proteolytic activities in YM seed were lower than in MJ seed. These results imply that energy depletion was the main reason for the decreased rate of germination and that this depletion inhibited processes involved in seed germination, including de novo synthesis of the proteins necessary for germination.